STRATEGIES FOR DRIVING AND DEVELOPMENT OF COMPUTATIONAL THINKING SKILLS OF STUDENTS IN BANNONGBOUY SCHOOL UNDER PHETCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Kunngern, Chaiyatis; Boonsong, Kanchana (Journal of MCU Phetchaburi Review, 2023)
Global changes in the 21st century have focusing on developing skills in various areas, one of which is an important skill is problem-solving skills. using computational thinking skills can be used to solve problems step by step and systematically. The researcher conducted this research with the objectives of 1) to study strategies for driving development of computational thinking Skills. 2) to study strategies for development of computational thinking Skills. And 3) to study results of development of computational thinking Skills. The target group was 3 teachers and 45 grade 1-3 students. The tools used in this research were: a manual strategies for driving and development of computational thinking skills of students. Quiz measurement computational thinking Skills of students before and after use strategies for driving development of computational thinking Skills of students and Interview form for research. Instrument consistency the value is between 0.67 - 1.00. Quantitative data analysis was statistical, arithmetic mean, progress percentage, standard deviation. The results of this research were as follows: 1) Strategies used in driving of computational thinking skills of students in Bannongbouy School under Phetchaburi Primary Educational Service Area Office 2. There are 3 strategies: Participation Strategy, Empowerment strategy and Integration strategy. 2)Strategies used by teachers development of computational thinking Skills of students is the LIPP strategy, consisting of 4 steps: Learning , Ideas , Plan and Piece and Estimate. 3) The results of developing computational thinking skills before and after the use of strategies for driving and development of computational thinking skills of students in Bannongbouy School under Phetchaburi Primary Educational Service Area Office 2 it was found that mean before used the strategy was 8.07 the standard deviation was 1.77 and mean after used the strategy was 16.42 the standard deviation was 1.60 and progress percentage to 41.75 The results of the interviews for the opinions of teachers and students found that teachers and students have fun with the activities this handbook is a useful guide that can help developing computational thinking skills and can be further applied to learning in each subject and other activities as well. The findings of this research show that Teachers will be able to develop students with computational thinking skills to succeed. There must be a strategy for drive every strategy together according to the plan set out.